2014
DOI: 10.1007/s12603-014-0034-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of the elderly in rural North China: A cross-sectional study

Abstract: As China's economic climate has developed, the nutritional status of elderly people in the rural parts of the country has improved in some aspects. However, the trend toward obesity will lead to a shift in the burden of obesity-related chronic diseases. In addition, rurally-located elderly people are at high risk of death that may be associated with abnormal serum cholesterol. The data also suggest that severe deficiencies in folate and vitamin B12 levels exist, as well as there being a high prevalence of hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
1
4
2
1
Order By: Relevance
“…Several studies regarding hyperhomocysteinemia were conducted in China. Compared to the study of Wang et al in East China (10.5 μ mmol/L, 45–75 years) [ 13 ], our study revealed a higher Hcy mean (24.6 μ mmol/L) [ 20 ]. Hao et al also showed lower Hcy medians (8.8 μ mmol/L for South China and 11.4 μ mmol/L for North China) [ 26 ] than ours (19.3 μ mmol/L) [ 20 ].…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Several studies regarding hyperhomocysteinemia were conducted in China. Compared to the study of Wang et al in East China (10.5 μ mmol/L, 45–75 years) [ 13 ], our study revealed a higher Hcy mean (24.6 μ mmol/L) [ 20 ]. Hao et al also showed lower Hcy medians (8.8 μ mmol/L for South China and 11.4 μ mmol/L for North China) [ 26 ] than ours (19.3 μ mmol/L) [ 20 ].…”
Section: Discussioncontrasting
confidence: 95%
“…Compared to the study of Wang et al in East China (10.5 μ mmol/L, 45–75 years) [ 13 ], our study revealed a higher Hcy mean (24.6 μ mmol/L) [ 20 ]. Hao et al also showed lower Hcy medians (8.8 μ mmol/L for South China and 11.4 μ mmol/L for North China) [ 26 ] than ours (19.3 μ mmol/L) [ 20 ]. However, the prevalence of PD in this area was not higher than that on behalf of China (1%, ≥55 years) [ 21 ], which indicated that Hcy may be not involved in the pathogenesis of PD.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Both groups had intakes well above the Chinese RNI for vitamin B-12 of 2.4 μg/d ( 26 ). In other parts of China, prevalence of low vitamin B-12 concentrations has ranged from 13.5% in Shanghai (deficiency defined as <139 pmol/L) ( 33 ) to 74.5% in rural North China (deficiency defined as <185 pmol/L) ( 34 ). To our knowledge, there are currently no data available on the vitamin B-12 status in the general population aged 50 y or older living in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
“…En el presente estudio no se observó tal asociación RP 1,22 (IC95%: 0,72 -2,04; p= 0,444). Otra asociación importante es la hipocolesterolemia así lo demuestra Zhang et al, China 2015, quien asocia hipocolesterolemia y malnutrición p<0,001 22 . En el presente estudio tampoco se observó tal asociación RP 1,55 (IC95%: 0,95-2,52 p= 0,077).…”
Section: Discussionunclassified